Education Supply Chain Management Model to Achieve Sustainability in Private Universities in Malaysia: A Review - Govindaraju Basu; John Jeyasingam; Md. Mamun Habib (International Journal of Supply Chain Management, 2016)
This paper addresses an Integrated Tertiary Educational Supply Chain Management Model (ITESCM) to achieve sustainability among private universities in Malaysia. The application model highlights the role of Supply chain management and sustainable practices in Private Universities (PU). The model provides an overview to equip stakeholders of the educational supply chain with appropriate information to review and appraise the performance of private universities. This is with a view towards the fulfillment of ultimate goals in achieving the potential as providers of educational supply chain services and maintaining sustainability. The paper first provides an overview of recent research conducted in this area, followed by a detailed discussion on research issues that have been developed in ITESCM. It also provides the taxonomy of research and development in the area of integrated SCM and sustainability practices in higher education, particularly in private universities in Malaysia. The concept of integration in tertiary education supply chain and sustainability among private university is also discussed.